Use of block copolymers and surfactants for the dispersion of CNTs - Becker, Daniela (2013)
After the report in carbon nanotubes (CNTs) by Iijima, a new era in nanocomposites and nanomaterials started. In order to reach the full potential of the use of CNTs several challenges must be overcome, especially three of them: (1) homogeneous dispersion; (2) stabilization of the dispersion in a media; and (3) stronger interface between the CNTs and media. By the middle of the 1990s, block copolymers (BCPs) started to be seen as a tool for that self-assembly of either molecular or non-molecular components by non-covalent interactions enabling the preparations of nanostructures accessible only by covalent methods. In some cases BCPs can either stabilize suspensions or induce more homogeneous dispersion of nanostructures in dense media or even as a toughening agent for thermosets. By the end of 1990s the role of surfactants for dispersing and stabilizing CNTs suspensions started to be studied. Initially, the focus was on aqueous and/or organic media, later on polymeric matrices. Several studies in the literature pointed out the potential of surfactants to stabilize solutions and to improve the interface/interphase of nanostructures/media. This paper offers a concise review of recent advances in the use of surfactants and BCPs for dispersing and stabilizing CNTs in several different media. Finally, some attention is given to applications with nanocomposites where thermosets are used as matrices. © 2013 Bentham Science Publishers.